THE RELATIONSHIP BETWEEN EATING DISORDERS AND NUTRITIONAL STATUS IN ADOLESCENTS - Arfah, Muh.; Devy, Shrimarti Rukmini; Qomaruddin, Mochammad Bagus; Amir, Eby Ramdhani; Zari, Afina Puspita; Rahmani, Alinda (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
Background: The changes that occur during adolescence can lead to various issues, including nutritional status problems. Some indirect causes of nutritional problems are related to eating disorders. Eating disorders are psychiatric syndromes characterized by deviant eating patterns associated with psychological characteristics related to food, body shape, and weight. Purpose: The aim of this study is to determine the relationship between eating disorders and nutritional status among students of SMAN 4 Maros, Maros District in the year 2023. Methods: This research is an observational study that observes phenomena or events occurring in the research subjects, using a cross-sectional design. The population of this study consists of 281 students, with a sample size of 165 student respondents from SMAN 4 Maros District. Results: The results of the study indicate that there is a relationship between eating disorders and nutritional status among students of SMAN 4 Maros District, with a p-value of 0,00 < 0,05 Conclusions: The conclusion drawn from this research is that eating disorders are related to the nutritional status of adolescents in SMAN 4 Maros, Maros District in the year 2023. This study suggests that students of SMAN 4 Maros should adopt healthy eating behaviors to prevent eating disorders.